They called him the «golden pen» of Spain - Andrey Silin (Ибероамериканские тетради)
The article, written as literary and historical essay, is dedicated to the destiny of the talented writer and journalist Mariano José de Larra, who left the brightest trace in the history and culture of Spanish society of the nineteenth century.